Electrochemical In Situ Formation of a Stable Ti‐Based Skeleton for Improved Li‐Storage Properties: A Case Study of Porous CoTiO3 Nanofibers. Issue 36 (9th June 2017) - Liu, Si‐Yu; Fan, Chao‐Ying; Wang, Han‐Chi; Zhang, Jing‐Ping; Wu, Xing‐Long
Abstract: Bimetallic transition‐metal oxides, which exhibit superior electrochemical properties compared with pristine single‐metal oxides, have recently become a topic of significant research interest for applications in lithium‐ion batteries (LIBs). Herein, we report a simple and scalable electrospinning method to synthesize porous CoTiO3 nanofibers as the precursor for nanostructured bimetallic transition‐metal oxides formed electrochemically in situ. This strategy ensures uniform mixing and perfect contact between two constituent transition‐metal oxides during the lithiation/delithiation process. Furthermore, CoTiO3 nanofibers based on ultrafine CoTiO3 nanocrystals are interconnected to form a nano/microstructured 3D network, which ensures the high stability of the in situ formed structure composed of bimetallic transition‐metal oxides, and also fast ion/electron transfer and electrolyte penetration into the electrode. Electrochemical measurements revealed the excellent lithium storage (647 mAh g −1 at 0.1 Ag −1 ) and retention properties (600 mAh g −1 at 1 Ag −1 after 1200 cycles) of the CoO/TiO2 electrode. Moreover, the electrochemical reaction mechanism was explored by using ex situ X‐ray photoelectric spectroscopy and cyclic voltammetry tests, which confirmed the two‐phase reaction processes in the electrodes. These results clearly validate the potential of CoTiO3 with a unique nano/microstructured morphology as the precursor for a bimetallic transition‐metal oxide for use as the anode material for long‐life LIBs. Abstract : Anodes go bimetallic : On cycling of as‐prepared 3D CoTiO3 nanofibers, during the first lithiation process, along with the formation of a Li2 O matrix, Ti IV and Co II species were converted/reduced to Li x TiO2 nanoparticles (NPs) and metallic Co NPs, respectively, which suggested the electrochemical in situ formation of bimetallic transition‐metal oxides (see figure).